2018
DOI: 10.18203/2349-2902.isj20184069
|View full text |Cite
|
Sign up to set email alerts
|

A clinical study of platelet rich plasma versus conventional dressing in management of diabetic foot ulcers

Abstract: Background: Diabetic foot ulcers continue to pose significant global issue despite the advances made in the management of diabetes. It causes major foot complications if they are not addressed properly. It needs multidisciplinary approach for its care. While several advancements has taken place in wound care management, platelet rich plasma and stem cell therapy promises to offer a new hope in its management, aiding in cellular and tissue regeneration. The purpose of the present study was to compare Platelet-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…We found that common site was mid foot seen in 35 and 30 in group II, fore foot seen 20 in group I and 18 in group II, hind foot seen 5 in group I and 12 in group II. Prakasam et al [10] compared Platelet-Rich Plasma versus conventional dressing in the management of diabetic foot ulcers. Group A received conventional ordinary dressing (N=10, 50%) and Group B received PRP dressing (N = 10, 50%).…”
Section: Discussionmentioning
confidence: 99%
“…We found that common site was mid foot seen in 35 and 30 in group II, fore foot seen 20 in group I and 18 in group II, hind foot seen 5 in group I and 12 in group II. Prakasam et al [10] compared Platelet-Rich Plasma versus conventional dressing in the management of diabetic foot ulcers. Group A received conventional ordinary dressing (N=10, 50%) and Group B received PRP dressing (N = 10, 50%).…”
Section: Discussionmentioning
confidence: 99%